2013
DOI: 10.1007/s00774-013-0470-9
|View full text |Cite|
|
Sign up to set email alerts
|

Lysophosphatidic acid stimulates osteoclast fusion through OC-STAMP and P2X7 receptor signaling

Abstract: Bone is continuously remodeled by bone formation and resorption, and cooperative bone metabolism is precisely regulated to maintain homeostasis. Osteoclasts, which are responsible for bone resorption, are differentiated through multiple steps that include cell fusion at the last step of differentiation, yielding multinuclear cells. However, the factors involved in and the precise mechanism of cell fusion are still unknown. To determine the molecules involved in osteoclast fusion, we examined the effect of lyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Phosphatidic acid, LPA and DAG are involved in many membrane fusion and membrane fission events, such as fission of Golgi membranes , fission during endocytic transport , vacuole fission and fusion , mitochondrial dynamics , exocytosis , vesicle‐vesicle fusion , myoblast fusion , osteoclast fusion , membrane fusion during sporulation , membrane fusion during fertilization . Fusion of PA‐containing vesicles was studied in Refs .…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidic acid, LPA and DAG are involved in many membrane fusion and membrane fission events, such as fission of Golgi membranes , fission during endocytic transport , vacuole fission and fusion , mitochondrial dynamics , exocytosis , vesicle‐vesicle fusion , myoblast fusion , osteoclast fusion , membrane fusion during sporulation , membrane fusion during fertilization . Fusion of PA‐containing vesicles was studied in Refs .…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
“…Phosphatidic acid, LPA and DAG are involved in many membrane fusion and membrane fission events, such as fission of Golgi membranes [140,162,163,[165][166][167][168][169], fission during endocytic transport [170,171], vacuole fission [172] and fusion [132,147,[173][174][175], mitochondrial dynamics [17,40,95,[176][177][178][179][180][181][182][183][184][185], exocytosis [30,40,76,79,125,[186][187][188][189][190][191][192][193][194], vesicle-vesicle fusion [164], myoblast fusion [195,196], osteoclast fusion [197], membrane fusion during sporulation [198][199][200][201], membrane fusion during fertilization [202,203]. Fusion of PA-containing vesicles was studied in Refs [87,…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
“… 25 LPA also enhances differentiation of osteoclast precursors and regulates the morphology, resorptive activity, and survival of mature osteoclasts. 26 28 Therefore, LPA, LPA signaling, and LPA target molecules may be diagnostic and therapeutic targets to treat patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors speculate that ATP release via the P2X7R pore is needed for osteoclastic fusion, although the effect may be indirect involving other purinergic receptors. Since then, the role of P2X7R in driving LPA-stimulated osteoclast fusion has been highlighted (Hwang et al 2013). The authors showed that siRNA-induced P2X7R knockdown in RAW 264.7 cells downregulated the expression of osteoclastic functional makers including nuclear factor of activated T cells 1 (NFATc1), cathepsin K, tartrate-resistant acid phosphatase (TRAP), AT6v0d2, c-Src, c-Jun, and Car2, in addition to suppression of the LPA-stimulated increase in osteoclast Effect of P2X7R on osteoclastogenesis: extracellular ATP induces commitment of haematopoietic stem cells (HSCs) towards a more committed, myeloid progenitor/pre-osteoclast cell.…”
Section: Mature Cellsmentioning
confidence: 99%